Exploring the Root Cause for Chronic Kidney Disease of Unknown Etiology (CKDu) via Analysis of Metal Ion and Counterion Contaminants in Drinking Water: A Study in Sri Lanka - W. P. R. T. Perera; M. D. N. R. Dayananda; J. A. Liyanage (Journal of Chemistry)
The introduction of elevated amounts of foreign ions into the blood may lead to impairment of the filtration membrane of kidneys and chronic kidney damage. In order to assess the risk of consumption of drinking water (dug well water) in chronic kidney disease of unknown etiology (CKDu), affected areas in Sri Lanka, trace metals, and other counterions in water samples obtained from dug wells were analyzed and compared with a reference area. Drinking water could be the major source that is responsible for entering nephrotoxic ion contaminants into the human body. To achieve the objective, drinking water samples were collected from dug wells in two CKDu endemic areas and a reference area where no CKDu patients were found in a dry season. In the Wewelketiya area (one of the endemic areas), Cd concentrations in 60% of water samples and Pb concentrations in 40% of water samples have exceeded the maximum limit given by Sri Lanka water quality standards. Fluoride concentrations also have exceeded the permissible limits of more than 80% of collected water samples in both CKDu endemic areas. However, none of the water samples in reference areas has reported that Cd, Pb, and fluoride are beyond their maximum permissible limits. Hence, people in the particular CKDu endemic areas are at risk of kidney tissue damage due to long-term exposure to drinking water with elevated levels of some metal ions and counterions.